2014
DOI: 10.1155/2014/594350
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNA as Sepsis Biomarker Based on miRNAs Regulatory Network Analysis

Abstract: Sepsis is regarded as arising from an unusual systemic response to infection but the physiopathology of sepsis remains elusive. At present, sepsis is still a fatal condition with delayed diagnosis and a poor outcome. Many biomarkers have been reported in clinical application for patients with sepsis, and claimed to improve the diagnosis and treatment. Because of the difficulty in the interpreting of clinical features of sepsis, some biomarkers do not show high sensitivity and specificity. MicroRNAs (miRNAs) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 58 publications
(58 reference statements)
3
46
0
Order By: Relevance
“…However, only three similar miRs (miR-15b, miR-146a and miR-223) ( Table 1) were included in the five studies and only miR-146a was significantly decreased in patients with sepsis when compared with SIRS. Similar findings regarding miR146a were done with a 80% sensitivity for the sepsis diagnosis [28].…”
Section: Mirs As a Diagnostic Toolsupporting
confidence: 75%
See 1 more Smart Citation
“…However, only three similar miRs (miR-15b, miR-146a and miR-223) ( Table 1) were included in the five studies and only miR-146a was significantly decreased in patients with sepsis when compared with SIRS. Similar findings regarding miR146a were done with a 80% sensitivity for the sepsis diagnosis [28].…”
Section: Mirs As a Diagnostic Toolsupporting
confidence: 75%
“…However, this does not necessarily mean that no interaction is possible between changes of specific miRs and translational products. Recently, Huang J et al [28] identified ten miRs related to sepsis. After having searched databases for miR-mRNA interactions in several databases, they identified ten miRs that interact with specific genes and affects certain biological processes relevant for sepsis, such as apoptosis and macromolecule biosynthetic processes related to the cytokine cascade.…”
Section: Discussionmentioning
confidence: 99%
“…According to the statistical evidences described in our previous work, miRNAs with larger NOD and TFP values were more likely to be candidate biomarkers and represented biomarker miRNAs that had strong abilities to regulate genes independently and, meanwhile, regulate more TF genes. The application of biomarker discovery for prostate cancer [23, 25], sepsis [26], clear cell renal cell carcinoma [27], and pediatric acute myeloid leukemia [24] demonstrated its great predictive power.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the validity of miRNAs as biomarkers for sepsis has been explored by Huang et al [42] using microarray expression profiles and miRNA regulatory network analysis. The authors analyzed the expression profiles of miRNAs from various studies through validation and prediction databases such as TarBase and HOCTAR, and measured statistical significance with the student t-test.…”
Section: Extracellular Micrornas As Potential Biomarkers In Sepsismentioning
confidence: 99%